(3GdSdhGfGJ aj eSGeQg GdNdaGA hGdSGOGJs - (3MLI GdOjf GdUbdj , eMeO Hf CHj eMeO Hf XaQ, CHh YHO Gddg,J (B550 (3g` s
(3ChdgG (B:s
(3hHYO aEf eeG CbVi Edjg EVWQGH GdCZJGH hGdKjGH GdSdhGfI GdChdi hgj SdhGfI GdJbhjV s
(3BNQgG (B:s
(3ceG CSJYjfg ef Zhd GdLhGH hGSJQLY Hg aSGO GdNWGH ceG CSJQLY cSGO GdUhGH hCJhH Edjg agh QMje JhGH fLR GdcJGH hGdMeO ddg GdPi HfYeJ JJe GdUGdMGJ Gddge Udi Ydi SjOfG eMeO hBdg hUMHg hSde s
(3HgG QShe hCdhGf JMci UhQI cd McGjIs
(3fSNI bOjeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B205s
(3eUOQ GbJfGA GdCUd (B:s
(3eOQjO (B(528) s
Keywords: (3GdCOHs